'It's off to work we go!' Person–environment fit and turnover intentions in managerial and administrative mining personnel. Issue 3 (3rd July 2019) - Morrow, Rachel; Brough, Paula
Abstract : Purpose . Person–environment fit asserts that incompatibility between an employee and aspects of their work environment is more likely to lead to occupational stress. The aim of this study was to investigate the impact that varying levels of person–environment fit had on key criterion outcomes including work engagement, work-related wellbeing and turnover intentions in a unique sample of managerial and administrative mining personnel. Method . An online self-report survey was distributed to an Australian mining organization by the company's Chief Executive Officer. Anonymous survey links were sent to staff, of which 118 participants responded. The survey consisted of previously validated measures. Results . Hierarchical multiple regression analyses revealed significant relationships between abilities–demand fit, needs–supply fit and work engagement. Additionally, work-related wellbeing was significantly associated with increased person–organization fit and needs–supply fit. However, only needs–supply fit had a significant negative relationship with turnover intentions. Needs–supply fit significantly predicted all criterion variables. Conclusions . This study found that personal need fulfilment through work-related activities had the most significant impact on work-related wellbeing and work engagement. Personal need fulfilment through work also produced the most significant negative relationship with turnover intentions.